2014
DOI: 10.1172/jci72039
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 regulates memory CD8+ T cell O-glycan synthesis and affects trafficking

Abstract: Memory and naive CD8 + T cells exhibit distinct trafficking patterns. Specifically, memory but not naive CD8 + T cells are recruited to inflamed tissues in an antigen-independent manner. However, the molecular mechanisms that regulate memory CD8 + T cell trafficking are largely unknown. Here, using murine models of infection and T cell transfer, we found that memory but not naive CD8 + T cells dynamically regulate expression of core 2 O-glycans, which interact with P-and E-selectins to modulate trafficking to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 54 publications
6
78
0
Order By: Relevance
“…Our finding that P-selectin binding cells persist into the memory phase after influenza virus infection demonstrates that, unlike for CD8 + memory cells (40), fucosylation can be maintained on CD4 + T cells after the resolution of the response, consistent with a previous report that epigenetic modifications can sustain Fut7 transcription (26). It has been suggested that maintenance of selectin binding activity could distinguish effector memory from central memory cells that have a greater capacity for self-renewal in the lymphoid compartment (10).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that P-selectin binding cells persist into the memory phase after influenza virus infection demonstrates that, unlike for CD8 + memory cells (40), fucosylation can be maintained on CD4 + T cells after the resolution of the response, consistent with a previous report that epigenetic modifications can sustain Fut7 transcription (26). It has been suggested that maintenance of selectin binding activity could distinguish effector memory from central memory cells that have a greater capacity for self-renewal in the lymphoid compartment (10).…”
Section: Discussionsupporting
confidence: 91%
“…2J, K and Supplementary Tables 1 and 2). Similarly, five genes implicated in migration were DDR-regulated: GCNT1, CD44, LIMA1, CD34 and integrin 10 (ITGA10) (Wenke et al, 2006;Abe and Takeichi, 2008;Flynn et al, 2013;Nolz and Harty, 2014), but only CD34 was also VEGFA-regulated (Fig. 2J, K and Supplementary Tables 1 and 2).…”
Section: Vegfa and Ddr Elicit Distinct Transcriptional Patterns Linkementioning
confidence: 86%
“…Systemic and local inflammatory signals introduced by surgical procedures may alter the migration of circulating memory T cells as TCM cells are sensitive to inflammation-induced O-glycosylation and migration. 11 It is well documented that surgery has immediate impacts on the immune system of human patients. 79 Therefore, even as the golden standard in T RM research, the results from parabiosis experiments should be carefully interpreted along with the experiments involving less invasive procedures.…”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%
“…However, in contrast to the generally accepted notion that T EM cells patrol non-lymphoid tissues under steady state, recent studies have discovered that during local inflammation, T CM s, but not T EM s or long-lived effector T cells, migrate into inflamed tissues due to their superior capacity to induce O-glycosylation and generate P/E-selectin ligands, which facilitate the trans-endothelial extravasation of T cells. 10,11 Comparing with T EM , T CM cells generally express higher level of chemokine receptor CXCR3, which also enhances the migration of T CM into inflamed peripheral tissues. 12 Thus, the migration pattern of memory T cells is dynamically controlled by inflammatory signals independent of antigenic stimulation.…”
Section: Introductionmentioning
confidence: 99%